Cuproptosis: p53-regulated metabolic cell death? - Xiong, Chen; Ling, Hong; Hao, Qian; Zhou, Xiang (Cell death and differentiation, 2023)
Cuproptosis is a novel type of copper-induced cell death that primarily occurs in cells that utilize oxidative phosphorylation as the main metabolic pathway to produce energy. Copper directly associates with the lipoylated proteins of the tricarboxylic acid cycle, leading to the disulfide-bond-dependent aggregation of these lipoylated proteins, destabilization of the iron-sulfur cluster proteins, and consequent proteotoxic stress. Cancer cells prefer glycolysis (Warburg effect) to oxidative phosphorylation for producing intermediate metabolites and energy, thereby achieving resistance to cuproptosis. Interestingly, the tumor suppressor p53 is a crucial metabolic regulator that inhibits glycolysis and drives a metabolic switch towards oxidative phosphorylation in cancer cells. Additionally, p53 regulates the biogenesis of iron-sulfur clusters and the copper chelator glutathione, which are two critical components of the cuproptotic pathway, suggesting that this tumor suppressor might play a role in cuproptosis. Furthermore, the possible roles of mutant p53 in regulating cuproptosis are discussed. In this essay, we review the recent progress in the understanding of the mechanism underlying cuproptosis, revisit the roles of p53 in metabolic regulation and iron-sulfur cluster and glutathione biosynthesis, and propose several potential mechanisms for wild-type and mutant p53-mediated cuproptosis regulation.